Murillo en el siglo XIX: la Corona poética dedicada a Murillo (1863) y la corona de Montpensier, o el uso político de la devoción - Comellas, Mercedes (My University, 2019)
In 1863 was published in Seville the orona poética dedicada al insigne pintor sevillano Bartolomé Esteban Murillo, including celebratory poems of the most famous Andalusian poets of the time. The date of publication of the collection allows to use it as a point of reference to review Murillo's assessment from his romantic vision until the arrival of Realism, when he was relieved by Velázquez as the best painter in Spain. The analysis of the context in which the tribute was conceived shows the interested use that political intentions applied to devotion, but also to the «Sevillian school» in painting and poetry., En 1863 se publica en Sevilla una Corona poética dedicada al insigne pintor sevillano Bartolomé Esteban Murillo, reuniendo poesías celebratorias de las más conocidas plumas andaluzas de la época. La fecha de publicación de la colección permite usarla como punto de referencia para repasar la valoración de Murillo desde su visión romántica hasta la llegada del Realismo, cuando quedó relevado por Velázquez como mejor pintor de España. Además, el análisis del contexto en el que se gestó el homenaje demuestra el uso interesado que las intenciones políticas aplicaron a la devoción, pero también a la «escuela sevillana» en pintura y poesía.
Murillo in the Nineteenth Century: the Corona poética dedicada a Murillo (1863) and the crown of Montpensier, or the political use of piety
Keywords: Murillo; Velázquez; Nineteenth Century; Devotion; Montpensier; «Escuela sevillana»; Murillo; Velázquez; siglo XIX; devoción; Montpensier; «escuela sevillana»